2021
DOI: 10.1177/10783903211058785
|View full text |Cite
|
Sign up to set email alerts
|

Developing Competency-Based Nursing Treatment for Persons With Tobacco Use Disorder

Abstract: Background: Tobacco continues to have a deleterious impact on health outcomes in the United States. Professional nurses at all levels of practice have an opportunity to be a part of the solution. The development of nurse-specific competencies for treating tobacco use disorder (TUD) disorder is long overdue. A task force of American Psychiatric Nurses Association (APNA) subject matter experts was assembled to engage in the process of reviewing the available peer-reviewed literature and additional evidence-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…41 This is why failure to pay attention to improving the dimensions of competence in the profession leads to emotional damage to the individual and a decrease in the quality of care. 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 This is why failure to pay attention to improving the dimensions of competence in the profession leads to emotional damage to the individual and a decrease in the quality of care. 42…”
Section: Discussionmentioning
confidence: 99%
“…41 This is why failure to pay attention to improving the dimensions of competence in the profession leads to emotional damage to the individual and a decrease in the quality of care. 42 In past studies, the effect of training on the competence of nurses in providing PFA in disaster has not been investigated. However, supportive studies were found regarding the effect of PFA training on different dimensions of learning.…”
Section: Discussionmentioning
confidence: 99%
“…They are important factors that determine nurses’ behavior. To some extent, they will directly affect the quality and development of hospital nursing work [ 45 ]. The results of this study show that CBT can improve the critical thinking and innovation abilities, professional construction and development abilities of new nurses.…”
Section: Discussionmentioning
confidence: 99%